Peluang dan Tantangan Penerapan AI terhadap Manajemen Talenta pada SMK Negeri 1 Kota Banda Aceh - Mailisa Safitri, Husnaina; Agus Ariyanto; Mifta Salsabila; Liza Juannisyah (Politeknik Kampar, 2025)
This study analyzes the effect of Artificial Intelligence (AI) on talent management with competence as a mediating variable among students at SMK Negeri 1 Banda Aceh. The rapid development of AI technology influences talent management practices in vocational education. This research uses a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS 4. The sample consists of 150 students, selected using the Slovin formula. The results show that AI has a positive and significant effect on competence (beta = 0.658; T = 15.092; p-value < 0.05) and talent management (beta = 0.450; T = 7.199; p-value < 0.05). Competence also positively affects talent management (beta = 0.427; T = 7.151; p-value < 0.05). Furthermore, AI positively influences talent management through competence (beta = 0.281; T = 6.674; p-value < 0.05). These findings confirm that the use of AI improves competence and strengthens talent management in vocational education.